2007
DOI: 10.1097/inf.0b013e31813429fa
|View full text |Cite
|
Sign up to set email alerts
|

A New Combination Haemophilus influenzae Type B and Neisseria meningitidis Serogroup C-Tetanus Toxoid Conjugate Vaccine for Primary Immunization of Infants

Abstract: We conducted a phase 3 randomized controlled trial looking at the immunogenicity and safety of a novel combined Haemophilus influenzae type b and Neisseria meningitidis serogroup C tetanus toxoid conjugate vaccine, Hib-MenC-TT in a 2-, 3-, and 4-month primary infant immunization schedule. SBA MenC titers > or =1:8 and anti-PRP concentrations > or =0.15 microg/mL were measured in 99.2% and 100%, respectively, of the infants receiving Hib-MenC-TT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…GMC ratio DTPa-IPV group divided by DTPa+IPV group during infancy and childhood [20][21][22][23][24][25] in which the immunogenicity of DTPa-IPV was shown to be comparable to separate administration of existing commercially available DTPa-based and IPV-containing vaccines, with similar tolerability. Notably, the immunogenicity of the DTPa component of the vaccine was within the range previously reported in a Korean population, in which the seroprotection rates against diphtheria and tetanus and the seropositivity rates against pertussis antigens (PT, FHA and PRN) were [20][21][22][23][24][26][27][28][29] , and in 13 years of post-marketing experience when used for primary and/or booster vaccination. The present study demonstrates similar immunogenicity and tolerability in a Korean population, suggesting the vaccine will be similarly effective in preventing illness due to diphtheria, tetanus, pertussis and poliovirus.…”
Section: Discussionmentioning
confidence: 70%
“…GMC ratio DTPa-IPV group divided by DTPa+IPV group during infancy and childhood [20][21][22][23][24][25] in which the immunogenicity of DTPa-IPV was shown to be comparable to separate administration of existing commercially available DTPa-based and IPV-containing vaccines, with similar tolerability. Notably, the immunogenicity of the DTPa component of the vaccine was within the range previously reported in a Korean population, in which the seroprotection rates against diphtheria and tetanus and the seropositivity rates against pertussis antigens (PT, FHA and PRN) were [20][21][22][23][24][26][27][28][29] , and in 13 years of post-marketing experience when used for primary and/or booster vaccination. The present study demonstrates similar immunogenicity and tolerability in a Korean population, suggesting the vaccine will be similarly effective in preventing illness due to diphtheria, tetanus, pertussis and poliovirus.…”
Section: Discussionmentioning
confidence: 70%
“…The primary immunisation stage of this study has been reported elsewhere 11. Briefly, 500 healthy infants (mean age 8 weeks, SD 1.62, range 6–12 weeks) were randomised in a 3:1 ratio to the study group (Hib-MenC-TT group) vaccinated at 2, 3 and 4 months with DTPa-IPV (Infanrix-IPV, GlaxoSmithKline Biologicals, Rixensart, Belgium) and Hib-MenC-TT (Menitorix, GlaxoSmithKline Biologicals) or to the control group (MenC-CRM197 group) immunised with a corresponding three dose schedule of DTPa-IPV-Hib (Pediacel, Sanofi Pasteur, Lyon, France) and a MenC-CRM197 vaccine (Meningitec, Wyeth Lederle Vaccines, Pearl River, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Consent for both the primary and booster stages of this study was obtained from the parent or legal guardian at initial enrolment: details of ethical approvals, recruitment methods and inclusion and exclusion criteria have been reported elsewhere 11. For this booster stage additional exclusion criteria included previous booster vaccination against Hib or MenC, previous vaccination against MMR, and previous infection with Hib, MenC, measles, mumps or rubella.…”
Section: Methodsmentioning
confidence: 99%
“…There are currently monovalent group A or C, as well as several tetravalent groups A, C, W135 and Y (MCV4) conjugate vaccines available. Recently, a combined Haemophilus influenzae type B and N. meningitidis serogroup C conjugate vaccine has been licensed [53]. The introduction of conjugated serogroup C vaccines (MCC) into the routine childhood vaccination calendar in the UK and in several other European countries since 1999 has significantly reduced serogroup C-associated disease with relevant contribution of herd-immunity effects associated with conjugated vaccines [54,55].…”
Section: Available Vaccinesmentioning
confidence: 99%